Effective tricuspid regurgitation reduction is associated with renal improvement and reduced heart failure hospitalization - Felbel, Dominik; von Winkler, Juliana; Paukovitsch, Michael; Gröger, Matthias; Walther, Elene; Andreß, Stefanie; Schneider, Leonhard; Markovic, Sinisa; Rottbauer, Wolfgang; Keßler, Mirjam (Frontiers in Cardiovascular Medicine, 2024)
Background: Several studies have demonstrated an association between tricuspid regurgitation (TR) and organ dysfunction including hepatic and renal insufficiency. Improvement of liver function following transcatheter edge-to-edge repair (T-TEER) has already been linked to reduction of venous congestion due to TR reduction. This study analyzes whether TR-reduction using T-TEER is also associated with improved renal function. Methods and results: The TRIC-ULM registry includes 92 selected patients undergoing T-TEER between March 2017 and May 2023. Estimated glomerular filtration rate (eGFR) improvement was evident in 53 patients (57%) at 3-months follow-up (FU) and defined by FU eGFR > baseline eGFR. Median age was 80 [interquartile range 75 - 83] years, pre- and postinterventional TR grades were 4 [3-5] and 1 [1-2], baseline eGFR was 36 [30 - 53] ml/min and New Yeark Heart Association (NYHA) IV was evident in 15% of patients. Multiple logistic regression analysis revealed TR vena contracta reduction (Odds ratio (OR) 1.35 [95%-CI 1.12 – 1.64] per mm, p=0.002) and reduced preinterventional tricuspid annular plane systolic excursion (TAPSE) (OR 0.89 [95%-CI 0.79 – 0.99] per mm, p=0.033) to independently predict renal improvement at FU. An eGFR improvement threshold of >9 ml/min was associated with reduced 1-year heart failure hospitalization rates (adjusted hazard ratio 0.22 [95%-CI 0.07 – 0.62] p=0.005). Conclusion: Effective tricuspid edge-to-edge repair is associated with improved renal function and reduced heart failure hospitalization. In patients without renal improvement at 3-months follow-up, residual tricuspid regurgitation should be reevaluated for reintervention.